Pengaruh Human Capital terhadap Tingkat Kemiskinan di 13 Kabupaten Provinsi Jawa Tengah Tahun 2013-2022 - Muhammad Fahmi Yusuf; Banatul Hayati (Diponegoro Journal of Economics, 2024)
Poverty remains a serious issue in developing countries, including Indonesia. Central Java Province has become a focal point as one of the provinces in Indonesia with a high poverty rate, particularly in 13 districts where poverty levels are still above the national average. This study aims to explore how health and education affect poverty levels in these 13 districts. The research adopts a quantitative approach using panel data, covering the period from 2013 to 2022, and involving 13 districts in Central Java Province. The analysis method used is fixed effect model. The results show that the health variable, represented by life expectancy, has a significant negative effect on poverty levels. Similarly, the education variable, represented by the average years of schooling, also has a significant negative effect on poverty levels. However, unemployment shows a significant positive effect on poverty levels. Meanwhile, economic growth has no significant effect on poverty levels in the 13 districts of Central Java Province.